2017
DOI: 10.2147/pgpm.s131390
|View full text |Cite
|
Sign up to set email alerts
|

Association of the <em>PPP3CA</em> c.249G&gt;A variant with clinical outcomes of tacrolimus-based therapy in kidney transplant recipients

Abstract: BackgroundThe effects of genetic variants related to the pharmacodynamic mechanisms of immunosuppressive drugs on their therapeutic efficacy and safety have been poorly explored. This study was performed to investigate the influence of the PPP3CA c.249G>A variant on the clinical outcomes of kidney transplant recipients.Patients and methodsA total of 148 Brazilian patients received tacrolimus (TAC)-based immunosuppressive therapy for 90 days post-kidney transplantation. The PPP3CA rs3730251 (c.249G>A) polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In kidney transplant recipients on CNI-based immunosuppression, some polymorphisms in three calcineurin subunit genes ( PPP3CA , PPP3CB , and PPP3R1 ) were not associated with renal function and incidence of rejection or adverse events ( Moes et al, 2016 ; Pouché et al, 2016a ; Salgado et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…In kidney transplant recipients on CNI-based immunosuppression, some polymorphisms in three calcineurin subunit genes ( PPP3CA , PPP3CB , and PPP3R1 ) were not associated with renal function and incidence of rejection or adverse events ( Moes et al, 2016 ; Pouché et al, 2016a ; Salgado et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…However, polymorphisms in pharmacodynamics-related genes have been less explored in patients taking tacrolimusbased treatment (18,19). Our group investigated variants in genes related to calcineurin and mTOR signaling pathways and observed that MTOR, FKBP1A, FKBP2 and FOXP3 are associated with long-term impaired renal function, increased risk of acute rejection, and adverse events in kidney recipients treated with tacrolimus and everolimusbased immunosuppression (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…7 In this way, it inhibits the activation of mast cells and neutrophils and affects the function of basophils, eosinophils and Langerhans cells. 8…”
Section: Introductionmentioning
confidence: 99%